EFFECT OF TIME ANNEALING VARIATION ON MASS PERCENT OF Ag WITH THE EDX SPECTROSCOPIC - Abidin, Kurniati Kurniati (SAINFIS: Jurnal Sains Fisika, 2023)
The EDX spectroscopy is a test that aims to determined the composition of the elements contained in the test material. Therefore, in the synthesis of catalysts that require certain metals on the surface, characterization in important. Glass preparat (SiO2) as a substrate and Silver metal (Ag) as a source are deposited using the vacumm thermal evaporation method. The sample (SiO2/Ag) was then annealed at a temperature of 400 oC with variations in time annealing (15, 30 and 45 minute).The annaeling process causes a shift in the atomic of mass on the surface, resulting in a difference in the mass of Ag. However, on the other hand annealing aims to improve the surface structure. Of the three annealing time, the best time with the highest Ag composition occured at 30 minute. This time is estimated to occur at the stage of recrystallization of Ag material.